Anatomy and micromorphology of the endemic Gypsophila osmangaziensis (Caryophyllaceae) and taxonomic contributions for the genus Gypsophila - Ataşlar, Ebru; Ocak, Ati̇la (Phytotaxa, 2017)
Gypsophila osmangaziensis, an endemic species from Eskişehir (Turkey) is here studied from the anatomical and micromorphological points of view for the first time. Root, stem and leaf cross-sections as well as seed, leaf and pollen grains surfaces are investigated. Root shows perennial characteristics. Pericycle layer of the stem is composed of sclerenchymatic cells that have 15–17 very thick, layered cell walls. Leaf mesophyll is isobilateral and partly carries druse crystals. Seed surface has an obtuse tubercle. Pollen shape is oblate spheroidal.